2019
DOI: 10.1017/s0261444819000090
|View full text |Cite
|
Sign up to set email alerts
|

Theory and practice in language teacher education

Abstract: We often hear language teachers say ‘Don't confuse me with theories, just give me practical ideas I can take into the classroom’. Many teacher educators and researchers, on the other hand, believe that (research-based) theory is more important, and should be used and implemented by practitioners. This paper will propose an approach to the use of theory and practice in teacher education that may help to resolve this dissonance. After some preliminary definitions and clarification of some common confusions, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
2
16
0
2
Order By: Relevance
“…This finding resonated with Ur's (2019) point about learning and using language knowledge to teach. Ur (2019, p. 3) indicated that the language teaching and learning knowledge presented in academic publications could be helpful only when it enabled teachers to think, 'which [is] likely to result in useful learning and professional development', and not just for teachers to 'confine to' or fall back on. The pre-service teachers developed different learning activities and prepared different learning materials for teaching EFL reading.…”
Section: Understanding and Using Efl Knowledgementioning
confidence: 99%
“…This finding resonated with Ur's (2019) point about learning and using language knowledge to teach. Ur (2019, p. 3) indicated that the language teaching and learning knowledge presented in academic publications could be helpful only when it enabled teachers to think, 'which [is] likely to result in useful learning and professional development', and not just for teachers to 'confine to' or fall back on. The pre-service teachers developed different learning activities and prepared different learning materials for teaching EFL reading.…”
Section: Understanding and Using Efl Knowledgementioning
confidence: 99%
“…The label multilevel has been regarded differently among researchers. Namely, while some call multilevel, others such as Gurgenidze ( 2012), Ur (2019) and others tend to call them ´´mixed ability classes´´ when citing to these types of classes.…”
Section: First Factor: Ratio Of Teacher and Studentsmentioning
confidence: 99%
“…Writers had different interpretation about the word multilevel. Some writers such as Gurgenidze (2012) and Ur (2019) explained this kind of class using the term ´´mixed ability classes´´. Mathews-Aydinli & Horne (2006) specified that ´´typically, the label multilevel has come to describe classes where students from various levels, from beginning to advanced, are sited together in a single class".…”
Section: Introductionmentioning
confidence: 99%
“…La generalizzabilità pedagogica di quanto esporremo è certamente un limite non indifferente: come ben evidenziato da Spada (2019), è spesso difficile per gli insegnanti applicare adeguatamente alla loro prassi le indicazioni operative che vengono dalla ricerca. Ogni docente, infatti, esercita il suo "senso di plausibilità" (Ur 2019) in merito alle indicazioni pedagogiche che vengono dal mondo della ricerca, e così facendo discrimina fra attività possibili e utili e attività inadeguate a un determinato pubblico di studenti. Mantenendo saldo questo principio pragmatico e non necessariamente ottimale, anche facendo riferimento a lavori sperimentali passati raccogliamo in quanto segue alcune possibilità operative.…”
Section: Proposte Pedagogicheunclassified